Pengaruh Pemberian Kompos Cair Urine Sapi dan Pupuk NPK Terhadap Produksi Tanaman Kacang Tanah. (Arachis hypogaea L.) - Zulhadi Zulhadi; Syafrinal Syafrinal (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Cow Urine Liquid Compost is a waste nitrogen-containing compounds, water, minerals, hormone auxin and other metabolic products that are useful for plant growth. Giving liquid compost into the soil of cow urine is beneficial to improve soil structure and add the availability of nutrients in the soil. This research aims to determine the interaction of liquid composting of cow urine and NPK fertilizer on peanut crop production as well as to get the best dosage. This research was conducted at the Faculty of Agriculture, University of Riau from November 2016 until January 2017 using a randomized block design which consist of two factors and three replications, where: Factor I (dosing cow urine liquid compost) that is: without giving cow urine liquid compost, concentration of 20% with a dose of 1:38 l per plot, concentration of 30% with a dose of 1:38 l per plot and a concentration of 40% with a dose of 1:38 l per plot. Factor II (NPK), that is: without dosing NPK, 27 g per plot, 54 g per plot and 81 g per plot. Interaction of cow urine liquid compost and NPK showed a significant effect on number of primary branches and production per plot of peanut. The highest production of peanut crop obtained by giving cow urine liquid compost at concentration of 40% and NPK 81 and 54 g per plot with a yield that is 1291,8 - 1272.0 g per plot. Keywords: liquid compost, cow urine, NPK and peanuts